Problems and Prospects of Farmers in Sundarbans Delta (Mangrove Eco-system) of India - Das, Samares Kumar (International Journal of Bio-resource and Stress Management, 2023)
Sundarbans is such a unique region which is recognized as UNESCO World Heritage Site, a biodiversity hotspot with a treasure-trove of flora and fauna. It is a largest delta formed by a number of islands crisscrossed by uncountable rivers, creeks, rivulets. It is a largest and one of the few existing mangrove (halophytes) eco-systems in this world famous for the adobe of notorious infamous man-eating Royal Bengal Tiger. Inhabitants of such a wonderland struggle hard to earn a living. Salinity of the soil, lack of communication and other basic amenities, flood and storm cause havoc in this region. This article presents a ground-level reality of farmers in this region. Suggests possible solution as well as cautions that any strategy of development if adopted without a clear understanding of people’s perspectives empathetically will aggravate the situation instead improving it.